Learning and assessment with images: A view of cognitive load through the lens of cerebral blood flow. (21st June 2016) - Loftus, Jay J.; Jacobsen, Michele; Wilson, Timothy D.
Abstract: Understanding the relationship between cognitive processing and learner performance on tasks using digital media has become increasingly important as the transition towards online learning programs increases. Determining the impact of implementation of instructional resources is often limited to performance outcomes and comparisons to the status quo. This study measured changes in cerebral blood velocity (CBV) of the right middle cerebral artery during visual learning tasks using static images. Transcranial Doppler ultrasonography was used to compare the changes in CBV during learning of individuals with high and low spatial ability. Our results show that there is a slight increase from baseline values of CBV in individuals with high spatial ability during the learning task for the present study. In contrast, individuals with low spatial ability experience a decrement from baseline during the learning task. These results suggest spatial ability mitigates cognitive load and potentially has an impact on learner performance on visual learning tasks.